POSSIBILITIES OF USING THE HERITAGE OF THE ANCESTORS IN THE DEVELOPMENT OF STUDENTS' EDUCATIONAL ACTIVITY - M. Tajiboeva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The inheritance of ancestors provides an opportunity to expand the possibilities of a person, to research the theoretical and practical directions of his intellectual, spiritual and moral development. The system of using the didactic tools, methods and methods used by our thinking ancestors in the development of the educational activity of students is being formed.